STRATEGI BISNIS UNTUK MENINGKATKAN PENJUALAN JASA PENGIRIMAN KARGO FREIGHT FORWARDING - Andri Primadi; Dwi Meisyifa Kaoy; Yuliantini Yuliantini (Institut Transportasi dan Logistik Trisakti, 2017)
The aim of this study is to understand business strategic to increase sales of a freight forwarding company. Freight forwarding engaged in both export and import. Facing to competition every freight forwarding company must have a business strategy in order to increase sales of cargo delivery services. The strategy is designed through SWOT analysis by knowing internal (IFE) and external (EFE) factors of the company using 30 samples of Federal Express’ employees. In the SWOT analysis in increasing the company's cargo shipping service the company is positioned among Strenghts-Opportunity by harnessing the power to seize and exploit the greatest opportunities. Through the IE matrix, the company is in a position to grow and build alternative strategies that can be applied are forward integration, backward integration, horizontal integration, product development, market development, market penetration, and related diversification.